Analisis Pengendalian Mutu dan Kadar Logam Timbal pada Gula Kristal Putih di Pasaran Menggunakan ICP-OES - Febriana, Nina Kurnia; Wijayati , Nanik (Indonesian Journal of Mathematics and Natural Sciences, 2024)
Quality testing and determining levels of lead metal contamination have been carried out in samples of white crystal sugar sold on the market using the ICP-OES method. This test was carried out to evaluate the quality of white crystal sugar on the market and to determine the effectiveness of the ICP-OES method for analyzing lead metal contamination in white crystal sugar samples. The results of testing the quality (quality) of white crystal sugar, namely 8 samples of white crystal sugar meet the provisions of ICUMSA SNI 3140.3: 2020, 15 samples (all samples) meet the provisions of the maximum SO2 content of SNI 3140.3: 2020, 13 samples meet the provisions for drying shrinkage (moisture content) SNI 3140.3: 2020 and 6 samples met the white crystal sugar polarization provisions of SNI 3140.3: 2020. Meanwhile for the 5 samples that were analyzed for lead metal contamination levels, all samples showed results that the lead metal content did not exceed the maximum limit of SNI 3140.3: 2020 and for the linearity test it showed the linear coefficient (R2) value is 0.9999; LoD results of 0.002155 ppm; LoQ results of 0.007183 ppm; The accuracy results are shown by the %Recovery value of 95.21% and the precision results are shown by the %RSD value of 1.95%.